Analysis Of Factors Affecting Smeâ€™s Performance With Financial Capital And Network Abilities As Mediation Variables - Hatmawan, Aglis Andhita (APMBA (Asia Pacific Management and Business Application), 2020)
This study aims to determine the effect of entrepreneurship orientation and social capital on the performance of SMEs in the Garment industry in one of the largest city in the East Java Province in Indonesia, Madiun City. This research is an explanatory research with survey research design through quantitative approach. The population of this study are SMEs in the garment industry, specifically batik producers around Madiun City.Â  Cluster sampling area was used as sampling technique where 160 SMEs were used as the final sample in this study. Structured questionnaire was used as data collection method, while SEM and Sobel Test were used to analyze the hypothesis. The results of this study indicate that all hypotheses proposed in this study are accepted. There is a significant effect of entrepreneurship orientation on networking ability, and social capital on financial capital. There is a significant effect of networking ability on SME performance, as well as financial capital on SME's performance. The results of the mediation analysis using the Sobel test show the mediating role of networking ability and financial capital on the influence of entrepreneurship orientation and social capital on the performance of SMEs. This research contributes to the SME performance literature, it provides a deeper understanding of SME performance which includes how financial capital, entrepreneurship orientation, social capital and networking, can collectively improve business performance.